Principles of multilayer functional coatings creation by combined deposition methods - Drobyshevskaya, А.А. (Физическая инженерия поверхности, 2012)
The physical principles of the multilayer coatings formation by applying of combined deposition methods
of different thickness layers − plasma-detonation and ion-plasma are developed. This method of
composite coatings creating will allow receiving coatings with new properties and thus to improve of
product performance. Разработаны физические принципы формирования многослойных покрытий путем применения
комбинированных методов нанесения разных по толщине слоев – плазменно-детонационного
и ионно-плазменного. Рассматриваемый метод создания комбинированных покрытий позволит
получать покрытия с новыми свойствами и тем самым повысить эксплуатационные характеристики изделий. Розроблено фізичні принципи формування багатошарових покриттів шляхом застосування
комбінованих методів нанесення різних за товщиною шарів – плазмово-детонаційного та іонноплазмового. Метод створення комбінованих покриттів, що розглядається, дозволить отримувати
покриття з новими властивостями та тим самим підвищити експлуатаційні характеристики виробів.